Synthesis and Transformation of 5-Acetyl-2-aryl-6-hydroxybenzofurans into Furanoflavanone Derivatives - Mphahlele, Malose J.; Olomola, Temitope O. (Synthesis, 2019)
Tandem palladium-catalyzed Sonogashira cross-coupling and heteroannulation of 3-bromo-2,4-dihydroxy-5-iodoacetophenone with arylacetylenes followed by the base-mediated Claisen–Schmidt aldol condensation of the intermediate 5-acetyl-2-aryl-7-bromo-6-hydroxybenzofurans with benzaldehyde derivatives afforded the corresponding linear 2-arylbenzofuranchalcone hybrids. The presence of the o-hydroxy-trans-α,β-unsaturated carbonyl moiety in the prepared furanochalcone hybrids facilitated acid-mediated cycloisomerization into the corresponding linear furanoflavanones. The structures of the prepared compounds were confirmed using a combination of spectrometric techniques complemented with single crystal XRD analysis.
Keywords: 3-bromo-2,4-dihydroxy-5-iodoacetophenone; Sonogashira cross-coupling; furanochalcones; furanoflavanones; X-ray